Asuhan Akupunktur Pada Penderita Osteoartritis Sendi Lutut di Klinik Saraf Kejepit dan Nyeri Center Bogor - Yoan Rizki Yani Pardede; Mayang Wulandari; Amal Prihatono; Ikhwan Abdullah (Universitas Malahayati Lampung, 2026)
ABSTRACT Osteoarthritis is a degenerative disease of the joints. It can affect all joints in the body; however, it most commonly involves the joints of the hands, knees, hips, and spine, and is characterized by cartilage degeneration within the joints. The symptoms of osteoarthritis are progressive in nature. Acupuncture works by activating nerve fibers, triggering anti-inflammatory responses, stimulating the release of endorphins to reduce pain, inhibiting oxidative processes that damage cartilage, and improving joint range of motion. This case study aimed to determine the benefits of acupuncture care for patients with osteoarthritis at the Klinik Saraf Kejepit dan Nyeri Center Bogor. The study was conducted as a single case study over six therapy sessions involving one female participant aged 55 years who suffered from knee osteoarthritis. Data collection techniques included observation (Wang), interviews (Wen), listening and smelling (Wen), and palpation (Qie), in accordance with the standards of Traditional Chinese Medicine. The selection of acupuncture points was based on the syndrome of Liver and Kidney Deficiency, with therapeutic principles focused on pain relief and tonification of the Liver and Kidney. The results of the therapy evaluation showed gradual and consistent improvement, as indicated by the resolution of knee pain, improved walking ability, enhanced sleep quality, and improvements in tongue and pulse examination. Keywords: Osteoarthritis, Knee Joint, Acupuncture Therapy. ABSTRAK Osteoartritis merupakan suatu penyakit degeneratif pada persendian. Osteoartritis dapat merusak semua sendi di tubuh, tetapi Osteoartritis paling sering memengaruhi sendi tangan, lutut, pinggang, dan tulang belakang, ditandai dengan penampilan kerusakan tulang rawan pada sendi. Gejala Osteoartritis bersifat progresif. Akupunktur bekerja dengan mengaktivasi serabut saraf, memicu respon anti-inflamasi, merangsang pelepasan endorfin untuk mengurangi nyeri, menekan oksidasi yang merusak tulang rawan, serta meningkatkan ruang gerak sendi. Penelitian studi kasus ini bertujuan untuk mengetahui manfaat Asuhan Akupunktur pada Penderita Osteoartritis di Klinik Saraf Kejepit dan Nyeri Center Bogor. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu orang partisipan perempuan berusia 55 tahun yang mengalami Osteoartritis lutut. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Defisiensi Hati dan Ginjal dengan prinsip terapi yang diterapkan adalah Hilangkan nyeri dan Tonifikasi Hati Ginjal. Hasil evaluasi terapi menunjukkan adanya perbaikan yang bertahap dan konsisten, ditandai dengan hilangnya nyeri lutut, membaiknya kemampuan berjalan, meningkatnya kualitas tidur, serta perbaikan hasil pemeriksaan lidah dan nadi. Kata Kunci: Osteoartritis, Sendi Lutut, Terapi Akupunktur.